Tamarack River Ghost : A Novel - Apps, Jerold W., 1934- (Book collections on Project MUSE., 2012)
"When journalist Josh Wittmore moves from the Illinois bureau of Farm Country News to the newspaper's national office in Wisconsin, he encounters the biggest story of his young career--just as the paper's finances may lead to its closure. Josh's big story is that a corporation that plans to establish an enormous hog farm has bought a lot of land along the Tamarack River in bucolic Ames County. Some of the local residents and officials are excited about the jobs and tax revenues that the big farm will bring, while others worry about truck traffic, porcine aromas, and manure runoff polluting the river. And how would the arrival of a large agribusiness affect life and traditions in this tightly knit rural community of family farmers? Josh strives to provide impartial agricultural reporting, even as his newspaper is replaced by a new Internet-only version owned by a former New York investment banker. And it seems that there may be another force in play: the vengeful ghost of a drowned logger who locals say haunts the valley of the Tamarack River."--Publisher's description